Spin chemistry for biology: fluorescence detection of magnetic field effects on flavin photoreactions - Evans, E (2016)
Magnetic fields as weak as the Earth’s can change the yields and/or kinetics of radical pair reactions even though the interaction energies involved are orders of magnitude smaller than kT at room temperature. Proposed as the source of the light-dependent magnetic compass in migratory birds, Magnetic Field Effects (MFEs) on chemical reactions can be understood by the radical pair mechanism (Chapter 1) and are thought to operate in flavin-containing protein photoreceptors in the retina. Numerous studies on flavin-based model systems of biological importance have shown MFEs under physiological conditions. In many instances, these effects are small and are only likely to be of any importance to the postulated chemical compass if the primary effects of the magnetic fields on the geminate radical pairs are further enhanced via yet unknown amplification mechanisms. In this thesis, a novel technique is introduced which measures MFEs on the prompt fluorescence of continuously photoirradiated flavin/electron donor model systems (Chapter 2). By exploiting the sensitivity of this method it is possible to probe the effects of the magnetic interaction characteristics within the radical pair as well as those of the embedding media. In Chapter 3, the flavin-ascorbic acid system and rare examples of Low Field Effects relevant for magnetosensitivity to weak magnetic fields under biologically relevant conditions are explored. The possibility for the chemical amplification of MFEs is demonstrated for cryptochromes and related model systems through experiment and simulation (Chapter 4-5). Under conditions of continuous photoexcitation, any change in the kinetics of radicals formed downstream to the geminate radical pair can significantly enhance the prompt field effect over the timescale of milliseconds and longer. Given the efficiency of amplification and the simplicity of its implementation, it is not inconceivable for nature to have adopted these effects for improved magnetoreception.